Carboxyhaemoglobin and pulmonary epithelial permeability in man. - Jones, J G (1983)
The effect of cigarette smoke exposure on pulmonary epithelial permeability was studied in 45 smokers and 22 non-smokers. An index of cigarette smoke exposure was obtained from the carboxyhaemoglobin concentration (HbCO%). Pulmonary epithelial permeability was proportional to the half-time clearance rate of technetium-99m-labelled diethylene triamine pentacetate (99mTc DTPA) from lung to blood (T1/2LB). The relationship between T1/2LB and HbCO% was hyperbolic in form and the data could be fitted to the quadratic formula (formula; see text) where the parameters a0, a1, and a2 represent respectively the asymptotic T1/2LB value at large carboxyhaemoglobin values and the slope and shape of the curve. The values of these parameters were a0 4.4 (2.6), a1 = 77.8 (15.5), and a2 -25.5 (9.7) (SE). This is the first demonstration of a dose-response relationship between carboxyhaemoglobin and an increased permeability of the lungs in man and provides a technique for identifying the roles of carbon monoxide and other cigarette smoke constituents in causing increased pulmonary epithelial permeability.